The Position and Relevance of Abu Al-A'la Maududi's Political Thoughts for Leadership Ethics in the Era Society 5.0 - Yudha, Gesit; Arini, Isti; ., Abdul Aziz; Hermanto, Agus; Anggitha, Roy (KnE Social Sciences, 2024)
The lack of a leader’s figure perceived by the citizens has become a social phenomenon in Indonesian society. There are secular pragmatic practices, political secularization, flexing, and hedonic lifestyles which are shown by the leaders and become their self-image.This study aims to analyze the contribution of Al Maududi’s thought to ethical leadership in the era of society 5.0. The design of this study is library research and the main data source is the literature, which was written by Al Maududi. This research traces the data through the book “Empat Istilah Pokok dalam Al-Qur’an” and the book “al-Khilafah wa al-mulk”. The leadership in Al-Maududi’s framework is the concept of theo-democracy which states that the leader is an individual who showed God’s sovereignty under God’s rule and has a social responsibility to accept criticism from the citizens. Al-Maududi’s framework of ethical leadership is that leaders should not enrich themselves with the power of their position. In regards to fulfilling SDG’s goals, leaders who can manage nature and human resources are needed. The leaders should know how to utilize the technology in managing the resources and be able to take the profit for the citizens’ well-being. Keywords: Al-Maududi, political thought, leadership in the era of society 5.0